The Jakarta Post’s Portrayal of the Police’s Perspective on the Murder Case by FS: A Critical Discourse Analysis - Abidah, Amelia Nur; Sutrisno, Adi (Deskripsi Bahasa, 2023)
Representation is defined as a method of investigating a specific thing seen through language, action, or voice, which has different ways of representing something. People can see how certain issues are represented in the way they are delivered or reported in various media, whether in written or spoken language. To discover goals and messages in mass media, a researcher employed the analysis of certain discourse through the consideration in the use of words, phrases, and clauses that are arranged within media. This present research investigated how Indonesian police is represented through The Jakarta Post regarding the murder case of one police agent which offers new explanation regarding the way a news media elaborates on the Indonesian police through the language reflection used by the media through the three-dimension model of Fairclough. A qualitative research methodology is employed together with the application of a three-dimensional level of Norman Fairclough CDA. The results indicated that The Jakarta Post is neutral, with no bias toward either party, the public society, or the policies. It depicts how the Indonesian police handled the case. However, it still indicates public mistrust in the action or irregularities in the investigation and autopsy results, as evidenced by the responses of specific organizations in it. === Representasi didefinisikan sebagai metode untuk menyelidiki satu hal tertentu yang dapat dilihat melalui bahasa, tindakan, atau suara, yang masing-masing memiliki cara yang berbeda dalam merepresentasikan sesuatu. Masyarakat dapat melihat bagaimana isu tertentu direpresentasikan dalam cara penyampaian atau pemberitaannya di berbagai media, baik tertulis maupun lisan melalui bahasa. Untuk menemukan tujuan dan pesan dalam media massa, penelitian dapat menggunakan analisis wacana tertentu melalui pertimbangan penggunaan kata, frase, dan klausa yang disusun dalam media. Penelitian ini menyelidiki bagaimana polisi Indonesia direpresentasikan melalui The Jakarta Post terkait kasus pembunuhan salah satu agen polisi, dimana akan menawarkan penjelasan baru mengenai cara media berita mengelaborasi polisi Indonesia melalui refleksi bahasa yang digunakan media melalui model tiga dimensi dari Fairclough. Metode deskriptif kualitatif digunakan bersama dengan penerapan level tiga dimensi AWK Norman Fairclough. Hasilnya menunjukkan bahwa The Jakarta Post netral, tidak memihak salah satu pihak, masyarakat umum, atau pihak polisi. Ini menggambarkan bagaimana polisi Indonesia menangani kasus tersebut. Namun, hal itu tetap menunjukkan ketidakpercayaan publik terhadap tindakan atau kejanggalan dalam penyelidikan dan hasil otopsi, terbukti dari tanggapan organisasi tertentu di dalamnya.